Groundwater Quality Evaluation in the Upper Part of the Mandali Basin - Abed Hussain, Tariq (Iraqi Journal of Science, 2023)
Mandali Basin is located between latitudes (33◦ 39 '00 "- 33◦ 54' 55") to the north and longitudes (45◦ 11 '00 "- 45◦ 40' 00") to the east, eastern Diyala province. The research study attributes hydrochemical properties groundwater upper part of the Mandali basin for 20 wells through the data from the analysis of the hydrological information bank of the General Directorate for drilling water wells 2007, hydrochemical study of the water tube wells for two seasons showed water surplus season (February) and season the water deficit (August) It's water colorless, odorless dominated by sulfate ion and sodium, and through hydrochemical formula and the type of water was found that most of the water area of study is the sodium sulfate type Na2SO4 and through the study of the origin of groundwater showed it that is atmospheric origin for two seasons. Through classification Schoeller show that the predominant chemical type for two seasons is sulphates. Either through the study of water for different purposes validity was shown that the groundwater and the seasons are not suitable for drinking and is suitable for industrial uses while it is valid for animal consumption and for the purposes of building and construction As for irrigation Most water samples are invalid accept wells (3,4,7,15 , 18,19) and for two seasons.